2020
DOI: 10.1002/jor.24670
|View full text |Cite
|
Sign up to set email alerts
|

Localized delivery of ibuprofen via a bilayer delivery system (BiLDS) for supraspinatus tendon healing in a rat model

Abstract: The high prevalence of tendon retear following rotator cuff repair motivates the development of new therapeutics to promote improved tendon healing. Controlled delivery of non-steroidal anti-inflammatory drugs to the repair site via an implanted scaffold is a promising option for modulating inflammation in the healing environment. Furthermore, biodegradable nanofibrous delivery systems offer an optimized architecture and surface area for cellular attachment, proliferation, and infiltration while releasing solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Four studies added different components on the PLGA scaffolds, among which one study [ 114 ] reported the addition of ibuprofen could control the release of drugs and promote the reconstruction of tendon tissue. Zhao, S [ 32 ] added basic fibroblast growth factor (bFGF) to the scaffold, and found that the added factor group had better results than the factor free scaffold group.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies added different components on the PLGA scaffolds, among which one study [ 114 ] reported the addition of ibuprofen could control the release of drugs and promote the reconstruction of tendon tissue. Zhao, S [ 32 ] added basic fibroblast growth factor (bFGF) to the scaffold, and found that the added factor group had better results than the factor free scaffold group.…”
Section: Resultsmentioning
confidence: 99%
“…Other anti‐inflammatories such as corticosteroids 38 may also be suitable to reduce inflammation in this model but will likely require further refinement to the optimal timing of release and dosage. Immune modulation may be possible through taking aspirin which inhibits inflammation and scarring in injured tendon through JNK/STAT3 pathway 39 or through novel biomaterials that deliver ibuprofen locally 40 . Higher levels of MMP in muscle may be tuned through diet supplementation following injury with vitamin D 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Immune modulation may be possible through taking aspirin which inhibits inflammation and scarring in injured tendon through JNK/STAT3 pathway 39 or through novel biomaterials that deliver ibuprofen locally. 40 Higher levels of MMP in muscle may be tuned through diet supplementation following injury with vitamin D. 41,42 The role of NFκB in tendinopathy has been recently explored. 43 Here, too, NFκB F I G U R E 4 Tendon repair increases expression of inflammatory genes and proteins in tendon 1-week post-injury.…”
Section: Discussionmentioning
confidence: 99%
“… 65 Since then, electrospun nanofibers have widely been tested as experimental constructs for tissue engineering research and have been proposed as scaffolds for not only the repair of tendons, 66 67 but also bone, 68 cartilage, 69 meniscus, 63 ligaments, 70 liver, 71 blood vessels, 72 nerves, 73 and for drug delivery. 74 …”
Section: Electrospinningmentioning
confidence: 99%